Multi-Model Domain Adaptation for Diabetic Retinopathy Classification - Zhang, Guanghua; Sun, Bin; Zhang, Zhaoxia; Pan, Jing; Yang, Weihua; Liu, Yunfang (Frontiers in Physiology, 2022)
Diabetic retinopathy (DR) is one of the most threatening complications in diabetic patients, leading to permanent blindness without timely treatment. However, DR screening is not only a time-consuming task that requires experienced ophthalmologists but also easy to produce misdiagnosis. In recent years, deep learning techniques based on convolutional neural networks have attracted increasing research attention in medical image analysis, especially for DR diagnosis. However, dataset labeling is expensive work and it is necessary for existing deep-learning-based DR detection models. For this study, a novel domain adaptation method (Multi-Model Domain Adaptation) is developed for unsupervised DR classification in unlabeled retinal images. At the same time, it only exploits discriminative information from multiple source models without access to any data. In detail, we integrate a weight mechanism into the multi-model-based domain adaptation by measuring the importance of each source domain in a novel way, and a weighted pseudo-labeling strategy is attached on the source feature extractors for training the target DR classification model. Extensive experiments are performed on four source datasets(DDR, IDRiD, Messidor and Messidor-2) to a target domain APTOS 2019, showing that MMDA produces competitive performance for present state-of-the-art methods for DR classification. As a novel DR detection approach, this paper presents a new domain adaptation solution for medical image analysis when the source data is unavailable.